Case Report: Refractory Autoimmune Gastritis Responsive to Abatacept in LRBA Deficiency - Boz, Valentina; Valencic, Erica; Girardelli, Martina; Pin, Alessia; Gàmez-Diaz, Laura; Tommasini, Alberto; Lega, Sara; Bramuzzo, Matteo (Frontiers in Immunology, 2021)
Primary immunodeficiency (PID) with immune dysregulation may present with early onset gastrointestinal autoimmune disorders. When gastrointestinal autoimmunity is associated with multiple extraintestinal immune system dysfunction the diagnosis of PID is straightforward. However, with the advent of next generation sequencing technologies, genetic defects in PID genes have been increasingly recognized even when a single or no extraintestinal signs of immune dysregulation are present. A genetic diagnosis is especially important considering the expanding armamentarium of therapies designed to inhibit specific molecular pathways. We describe a boy with early-onset severe, refractory autoimmune gastritis and biallelic mutations in the LRBA gene causing a premature STOP-codon who was successfully treated with CTLA4-Ig, abatacept, with long term clinical and endoscopic remission. The case underscores the importance to consider a monogenetic defect in early onset autoimmune disorders, since the availability of targeted treatments may significantly improve patient prognosis.